Use of Twitter Among Local Health Departments: An Analysis of Information Sharing, Engagement, and Action - Neiger, Brad L; Thackeray, Rosemary; Burton, Scott H; Thackeray, Callie R; Reese, Jennifer H (JMIR Publications, 2013)
BackgroundSocial media offers unprecedented opportunities for public health to engage audiences in conversations and collaboration that could potentially lead to improved health conditions. While there is some evidence that local health departments (LHDs) are using social media and Twitter in particular, little is known about how Twitter is used by LHDs and how they use it to engage followers versus disseminating one-way information. ObjectiveTo examine how LHDs use Twitter to share information, engage with followers, and promote action, as well as to discover differences in Twitter use among LHDs by size of population served. MethodsThe Twitter accounts for 210 LHDs were stratified into three groups based on size of population served (n=69 for less than 100,000; n=89 for 100,000-499,999; n=52 for 500,000 or greater). A sample of 1000 tweets was obtained for each stratum and coded as being either about the organization or about personal-health topics. Subcategories for organization included information, engagement, and action. Subcategories for personal health included information and action. ResultsOf all LHD tweets (n=3000), 56.1% (1682/3000) related to personal health compared with 39.5% (1186/3000) that were about the organization. Of the personal-health tweets, 58.5% (984/1682) involved factual information and 41.4% (697/1682) encouraged action. Of the organization-related tweets, 51.9% (615/1186) represented one-way communication about the organization and its events and services, 35.0% (416/1186) tried to engage followers in conversation, and 13.3% (158/1186) encouraged action to benefit the organization (eg, attend events). Compared with large LHDs, small LHDs were more likely to post tweets about their organization (Cramer's V=0.06) but were less likely to acknowledge events and accomplishments of other organizations (χ2=12.83, P=.02, Cramer's V=0.18). Small LHDs were also less likely to post personal health-related tweets (Cramer's V=0.08) and were less likely to post tweets containing suggestions to take action to modify their lifestyle. While large LHDs were more likely to post engagement-related tweets about the organization (Cramer's V=0.12), they were less likely to ask followers to take action that would benefit the organization (χ2=7.59, P=.02. Cramer's V=0.08). While certain associations were statistically significant, the Cramer's V statistic revealed weak associations. ConclusionsTwitter is being adopted by LHDs, but its primary use involves one-way communication on personal-health topics as well as organization-related information. There is also evidence that LHDs are starting to use Twitter to engage their audiences in conversations. As public health transitions to more dialogic conversation and engagement, Twitter's potential to help form partnerships with audiences and involve them as program participants may lead to action for improved health.